Utility of First Trimester Ultrasonography before 11 Weeks of Gestation: A Retrospective Study - Celen, Sevki (International Scholarly Research Network, 2012)
We showed the utility of first trimester ultrasonography before 11 weeks of gestation for antenatal followup. We retrospectively analyzed 1295 records of patients who underwent first trimester ultrasonography (transvaginal/abdominal) in our antenatal clinic in Ankara, Turkey. Maternal age, parity, gestational age, and maternal gestational history were compared with ultrasonographic findings. Patients were divided into 12 groups based on ultrasonographic diagnoses in the first ultrasonographic scan, and called for a control examination within 10 days if the diagnostic findings were abnormal. The data were statistically analyzed using Kruskal-Wallis and chi-square tests. We noted 81.3% patients to have single, viable, intrauterine pregnancies, while 18.7% had abnormal or complicated pregnancies with uterine anomalies, ovarian cysts, fibroids, or subchorionic hematomas. Normal and anembryonic pregnancies had significantly lower median diagnostic period in the control ultrasonography than in the first examination. First trimester ultrasonography before 11 weeks of gestation is valuable in determining pregnancy outcomes.